2020
DOI: 10.1002/path.5508
|View full text |Cite
|
Sign up to set email alerts
|

Podocytes present antigen to activate specific T cell immune responses in inflammatory renal disease

Abstract: Infiltration of activated T cells into renal tissue plays an essential role in inflammatory nephropathy. However, the mechanism enabling the renal recruitment and activation of T cells remains elusive. Here we report that inflammatory cytokine‐promoted antigen presentation by podocytes is a key for recruiting and activating specific T cells. Our results showed that diabetes‐associated inflammatory cytokines IFNγ and IL‐17 all upregulated expression of MHC‐I, MHC‐II, CD80 and CD86 on the podocyte surface. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…Interestingly, a study showed that IL-17 (and IFNγ) upregulated the expression of MHC-I, MHC-II, and co-stimulatory molecules (CD80 and CD86) on the podocyte surface. Moreover, under IL-17 stimulation, podocytes increased the uptake and processing of antigen, resulting in the presentation of its peptide on the cell surface (93). This fact brings robustness to the idea that, in part, naïve T cells can enter the kidney and continue, under local factors, in the path of differentiation and activation to Th17 (95,96).…”
Section: Activation and Differentiation Of Th17 Cellsmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, a study showed that IL-17 (and IFNγ) upregulated the expression of MHC-I, MHC-II, and co-stimulatory molecules (CD80 and CD86) on the podocyte surface. Moreover, under IL-17 stimulation, podocytes increased the uptake and processing of antigen, resulting in the presentation of its peptide on the cell surface (93). This fact brings robustness to the idea that, in part, naïve T cells can enter the kidney and continue, under local factors, in the path of differentiation and activation to Th17 (95,96).…”
Section: Activation and Differentiation Of Th17 Cellsmentioning
confidence: 86%
“…Regarding Th17 cells differentiation, it is also worth mentioning that podocytes, mesangial cells, and renal tubular epithelial cells can behave as antigen-presenting cells (89)(90)(91)(92). So, these intrinsic renal cells can alone trigger the local activation of Th17 cells after recognizing, processing, presenting eventual DAMPs that cross the glomerular filtration barrier, as seen in other kidney disease models (89,93,94). Interestingly, a study showed that IL-17 (and IFNγ) upregulated the expression of MHC-I, MHC-II, and co-stimulatory molecules (CD80 and CD86) on the podocyte surface.…”
Section: Activation and Differentiation Of Th17 Cellsmentioning
confidence: 99%
“…Organoids have been used in other contexts to study MHC-T cell receptormediated interactions between epithelial cells and T cells, and it was shown that intestinal stem cells expressing MHC II are non-conventional antigen-presenting cells (Biton et al 2018). These findings bear similarities to the expression of MHC I and MHC II on renal epithelial cells (Goldwich et al 2013;Li et al 2020). It remains to be determined whether MHC I and II expression by podocytes in iPSC-derived kidney organoids reflects their expression by podocytes in vivo; however, the potential to study T cell-podocyte interactions in an autologous system using blood-derived PBMCs from patients would importantly contribute to our understanding of these interactions in kidney diseases, including SLE.…”
Section: Lupus Nephritismentioning
confidence: 99%
“…However, studies suggest that epithelial cells such as podocytes and renal tubular cells also express HLA molecules and even regulate T cell activation (Wuthrich et al 1989;Frasca et al 1998;Banu and Meyers 1999;Yuan et al 2020). Podocytes express increased numbers of MHC I and II molecules upon stimulation with cytokines (Henny et al 1986;Goldwich et al 2013;Li et al 2020). In vitro and in vivo studies have shown that CD8 + T cells as well as CD4 + T cells can be activated by CD56 + CD80 + podocytes presenting antigens on MHC I or MHC II molecules (Goldwich et al 2013;Li et al 2020) and may contribute to the induction of dysregulated responses.…”
Section: Lupus Nephritismentioning
confidence: 99%
See 1 more Smart Citation